An overview on tuberculosis-specific hospitals in China in 2009: results of a national survey. Issue 5 (25th February 2016) - Pang, Yu; Du, Jian; Qin, Zhi Zhen; Greenwald, Zoë; Liu, Yuhong; Mi, Fengling; Zhao, Yanlin; Li, Liang
As of 2014, tuberculosis (TB) was the deadliest infectious disease worldwide and China has the third-highest TB burden [1]. In that year alone there were 826 155 new cases in China [1]. In addition, China has been experiencing a serious epidemic of drug-resistant TB [2, 3]. TB hospitals are critical for control of DR-TB, hence strengthened collaboration with public health systems is needed http://ow.ly/YnikY